From Washington to post-Washington? Consensus policies and divergent developments in Latin America and Asia - Rainer Schweickert; Rainer Thiele (Institut für Weltwirtschaft (IfW), 2004)
Most Latin American countries have made considerable progress in implementing the core recommendations of the Washington Consensus. The comparison with fast-growing Asian countries shows, however, that higher and more broadbased growth can only be achieved with more comprehensive reforms which contain four important additional elements. First, external stability should be given priority in order to support export activities. More flexible exchange rates and the prudent use of capital market policies could stabilize real exchange rates as well as capital inflows. At the same time, the need for capital inflows could be reduced by increasing domestic savings through higher government savings and efforts to overcome the segmentation of domestic capital markets. Second, the adoption of best-practice technologies should be encouraged in order to accelerate technical progress. Measures which could ease the transfer of technology are the use of FDI as a source of technology for export-oriented sectors and human capital formation with an emphasis on technical and job-related skills. More flexible labor markets could bring higher employment levels, which is important for mobilizing resources through learning-on-the-job. Third, poverty should be alleviated and inequality be reduced in order to broaden the participation of the population in economic activities and to facilitate the establishment of small and medium-sized firms. The highest priority should be given to a strong basic education system, labor market reforms which facilitate the migration from the informal sector to higher-paid formal employment, and a comprehensive titling program for land and property which allows access to the formal credit market. Fourth, the formal institutional framework should be reliable in order to guarantee a certain degree of predictability. Only then investors will have an incentive to undertake projects with a longer gestation period. In addition, the establishment of informal institutions (social capital) should be encouraged in order to reduce transaction costs. This can best be achieved indirectly by means of targeted support for the poor which reduces the extent of social exclusion and polarization, a higher level of education which raises the acceptance of norms transcending narrow kin groups, and better formal institutions which constrain the ability of the government to act arbitrarily. Taken together, export orientation, technology transfer, poverty alleviation, and institution-building could allow developing a more flexible economic structure and a more dynamic performance of investment and exports, which would in turn be reflected in higher and more equitable growth. In order to start such a process, the countries need to design their own strategies. This is because most reforms, especially institution-building, have to be tailored to domestic conditions. The poverty reduction strategy papers (PRSPs), which have to be set up by highly indebted poor countries (HIPC) in order to get debt reductions, could provide a blueprint for the development of national reform strategies.
Keywords: 330; Anpassungsprogramm des IWF; Wirtschaftsreform; Wirtschaftspolitische Wirkungsanalyse; Entwicklungskonvergenz; Armutspolitik; Bildungsinvestition; Institutioneller Wandel; Lateinamerika; Asien